Repercusión del abandono en el estado mental y emocional del adulto mayor que reside en el Asilo de Ancianos Hogar San José de la ciudad de Cariamanga - Pacheco Sánchez, Manuel Anibal (2016)
This research work was aimed to determine the presence of the impact on the mental and emotional state of the elderly residing in nursing home San Jose of the Cariamanga city. This research work was descriptive, transversal and a quantitative approach. Interview techniques was applied to the collection of information through a survey that was prepared and executed by the researchers and the application of the Test of Yesavage and Pfeiffer with their respective guidelines and questionnaires targeting 35 adults Home San Jose City Cariamanga that formed the sample. The results derived allowed to determine a high prevalence of emotional and mental disturbances caused mainly by the abandonment obtaining 57% of the population is within the parameters of mild depression, followed by 34% of established depression and 9% are considered emotional state normal . Also in cognitive or mental decline in older adults, they are described: 63% severe, 17% moderate; 11% and 9% is normal. Before the above was conducted an intervention aimed at the prevention of emotional disturbances and metals, by socialization of results to physicians and home care San Jose. Likewise gave a lecture with audiovisual teaching material and a manual on prevention, on the emotional state and cognitive impairment in older adults so that this situation is a matter of priority, to bring about improvements in the quality of life of the elderly. Finally concluding that the emotional and mental disorders are highly prevalent in the elderly as a result of neglect Keywords: elderly, emotional state, mental state